Roda Putar Efikasi Diri dan Video terhadap Efikasi Diri Pasien Kanker Payudara (Journal of Telenursing (JOTING), 2023)
This study aims to determine the comparison of health education through the Wheel of Self-Efficacy (ROPEDI) and videos on increasing the self-efficacy of breast cancer patients. The method employed is Quasi-Experimental with a pre and post-test design involving a control group. The research results indicate a p-value of 0.02, demonstrating a significant change in self-efficacy values across all three groups.  Further analysis tests (post hoc) showed that there was a change in the average value in the Rotating Wheel of Self-Efficacy (ROPEDI) group (26.08), the educational video group (25.67) and the control group (20.17). In conclusion, there is an influence of the Wheel of Self-Efficacy (ROPEDI) media and videos on increasing the self-efficacy of breast cancer patients. Keywords: Self-Efficacy, Breast Cancer, Self-Efficacy Spinning Wheel, Video